A133 GASTRIC ESD: PRELIMINARY EXPERIENCE IN A TERTIARY CENTER IN QUEBEC. (4th March 2021) - Maillet, D; Desilets, E; Maniere, T
Abstract: Background: Endoscopic submucosal dissection (ESD) is an endoscopic procedure developed in Asian countries to treat early gastric cancer (EGC). Western countries have less experience with this challenging technique. Aims: The goal of this study is to evaluate the effectiveness of ESD as a preliminary experience. Methods: This is an unicentric retrospective study of all consecutive gastric ESD for adenomas or EGC from 07/2017 to 08/2020. The primary endpoints were en bloc and R0 resection rates. Results: Nineteen patients (mean age 74.2 (54–88), sex ratio 3F/16M) and 23 lesions were included. Mean diameter was 25 mm (10–90). Treatment was previously performed in 7 cases (30.4%), by ESD (5) or EMR (2). The procedure, performed under general anaesthesia, lasted on average 148 minutes (45–412). En bloc resections were performed in 16 cases (69.6%); 5 cases (21.7%) were converted to P-EMR and there was a failure to resect the lesion because of deep invasion or perforation in 2 cases (8.7%). Pathologic examination demonstrated 2 low-grade dysplasia, 4 high-grade dysplasia and 15 adenocarcinomas: intramucosal (8), sm1 (2), sm2 (2), sm3 (1) or sm deep (2). R0 and curative resection rates were 43.5% and 39.1% respectively. The complication rate related to the procedure was 30.4% including 5 perforations and 2 delayed bleeding: all were managed endoscopically. Five patients (21.7%) underwent subsequent gastrectomy for non-curative resection (4) or failed resection (1); 3 had no residual disease on final pathology, 1 had high grade dysplasia and 1 had intramucosal adenocarcinoma. One patient went to palliative care because he was unfit for surgery. Follow-up endoscopy was completed in all 17 patients who underwent endoscopic resection (mean 10 months (2–24)). Recurrence occurred in 23.5% (4/17); all were successfully treated by another ESD. Conclusions: In our preliminary experience, the rate of en bloc and R0 resection were 70% and 44%. Compared to other studies, these low en bloc and curative resection rates may be explained by technically difficult lesions during the learning curve and might improve with experience. Nevertheless, surgery has been avoided in 13/19 patients (68%) with endoscopic intervention. Funding Agencies: None